Power supply for monitoring and metering devices of DC traction network based on serial chain of voltage converters - Yu. V. Plotnikov (Омский научный вестник)
When designing devices for monitoring and accounting of electric energy for railway traction networks of direct current, one of the main tasks is to create a source for their power supply. The paper considers the problems that arise when using power sources from the network of own needs of a traction substation, reviews the main technical solutions of sources powered from the traction network, and also offers an original solution that has a high efficiency compared to its prototype.